2018
DOI: 10.1002/chem.201706061
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic C−F Bond Activation with Alanes

Abstract: Hydrodefluorination reactions (HDF) of per- and polyfluorinated olefins and arenes by cheap aluminum alkyl hydrides in non-coordinating solvents can be catalyzed by O and N donors. TONs with respect to the organocatalysts of up to 87 have been observed. Depending on substrate and concentration, high selectivities can be achieved. For the prototypical hexafluoropropene, however, low selectivities are observed (E/Z≈2). DFT studies show that the preferred HDF mechanism for this substrate in the presence of donor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 90 publications
0
30
0
Order By: Relevance
“…the thermodynamically more stable E ‐isomer of 1,3,3,3‐tetrafluoropropene ( 5 b ) is preferentially formed. Such a high E / Z ratio is not observed in titanium‐, rare‐earth‐metal‐catalyzed or alane‐induced HDF reactions; a maximum E / Z ratio of 15 has been reported . Conversions of the HDF reactions with 1 a in diglyme and NEt 3 are similar (53–56 %, entry 2,3), but the selectivity is much higher when the reaction is conducted in NEt 3 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…the thermodynamically more stable E ‐isomer of 1,3,3,3‐tetrafluoropropene ( 5 b ) is preferentially formed. Such a high E / Z ratio is not observed in titanium‐, rare‐earth‐metal‐catalyzed or alane‐induced HDF reactions; a maximum E / Z ratio of 15 has been reported . Conversions of the HDF reactions with 1 a in diglyme and NEt 3 are similar (53–56 %, entry 2,3), but the selectivity is much higher when the reaction is conducted in NEt 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies towards aluminum hydrides in C‐F bond activation reactions showed that their reaction behavior coincide with the gallium hydrides. No or almost no HDF products could be observed for the HDF reactions with ( i Bu) 2 AlH ( 2 a ) or LiAlH 4 ( 2 b ) in toluene, but addition of catalytic amounts of donor molecules lead to high conversions (Table ). Comparison of the gallium hydrides 1 a and 1 b with corresponding aluminum hydrides 2 a and 2 b demonstrate that the reaction behavior of the ionic compounds 1 b and 2 b are similar: in the non‐coordinating solvent toluene the conversion is low, but addition of 10 mol % diglyme increases the conversion up to 100 % for 3 , 4 f and 7 (compare Table – with ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations